2020
DOI: 10.3389/fcell.2020.577032
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Coronavirus Disease 2019 (COVID-19) and Integrated Analysis SARS-CoV-2 Receptors and Potential Inhibitors in Lung Adenocarcinoma Patients

Abstract: The outbreak of novel coronavirus disease 2019 (COVID-19) has become the largest health threat worldwide, with more than 34.40 million positive cases and over 1.02 million deaths confirmed. In this study, we confirmed that significantly differentially expressed genes in COVID-19 patients were mainly involved in the regulation of immune and inflammation-related signaling pathways. It is worth noting that many infected COVID-19 patients have malignant tumors, and their prognosis is poor. To explore the susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Uddin et al investigated the association of ACE2 expression with immune signatures, immune ratios, and pathways in LUAD through the computational analysis of the expression profile of ACE2 in LUAD from the TCGA and GEO databases [11] . The work of Tang et al demonstrated the expression characteristics of ACE2, TMPRSS2, and AAK1 in LUAD and their influence on immune infiltration via differential expression analysis, enrichment pathway analysis, and the estimation of immune cell infiltration in LUAD [25] . However, the scientific mechanism underlying the high susceptibility of LUAD patients to COVID-19 had not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Uddin et al investigated the association of ACE2 expression with immune signatures, immune ratios, and pathways in LUAD through the computational analysis of the expression profile of ACE2 in LUAD from the TCGA and GEO databases [11] . The work of Tang et al demonstrated the expression characteristics of ACE2, TMPRSS2, and AAK1 in LUAD and their influence on immune infiltration via differential expression analysis, enrichment pathway analysis, and the estimation of immune cell infiltration in LUAD [25] . However, the scientific mechanism underlying the high susceptibility of LUAD patients to COVID-19 had not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yuan et al [58] showed that abiraterone acetate and bexarotene effectively inhibit SARS-CoV-2 replication in vitro. Bexarotene has also been shown as a potential drug target of ACE2, TMPRSS2, and AAK1 through bioinformatic analysis [59]. Thus, bexarotene could be regarded as a candidate drug for repurposing in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inhibition of AAK1 by Jaktinib hydrochloride which is also a broad-spectrum JAK (Janus kinase) inhibitor is shown to slow the proliferation of SARS-CoV-2 [ 51 ]. The expression level of AAK1 in COVID-19 patients is significantly decreased compared with normal subjects, suggesting that COVID-19 patients may consume a large amount of AAK1 in the late stage of the disease [ 52 ]. All of the evidence strongly suggests that Pharmacological suppression of Numb-associated kinases can be a potential strategy to treat COVID-19.…”
Section: Numb-associated Kinases As Potential Broad-spectrum Antivira...mentioning
confidence: 99%